Influence of ventilated enclosing structures on the regulation of house energy supply - Lymarenko, Oleksiy (Technology audit and production reserves, 2018)
The object of research is calculation of the value of the course of changes in the internal temperature in the investigated house with ventilated (VPS) and unventilated enclosing structures, where the two-stage regulation of the operation time of the heat point was used. Complex analysis of energy efficiency of the house, and first of all, of the enclosing structures, has been carried out. It has been demonstrated that regulation of the central heating can be used for additional energy savings. It is also possible to regulate depending on the climatic conditions, that is, the thermal power of the boiler or the heating point will depend on the change in the temperature of the air outside. It has been established that the use of scientifically substantiated proposals offered in the work significantly increases the thermal inertia of the enclosing structures. Due to this, when the heating system is switched off, the house is slowly cooled and heated relatively quickly. Thus, it is possible to get savings, as the structure elements of the building accumulate heat. The essence of optimum temperature control has been established, which is controlling the supply of heat energy in the room in such a way that the corresponding internal air temperature has been reached over a certain period of time. It has been found out that in order to achieve high energy efficiency of a building, in addition to its thermo-modernization, it is necessary to maintain the appropriate climatic conditions inside the heating premises. The factors that influence the ability to regulate the temperature inside the premises, depending on the change in the temperature of the air outside, have been established. The coefficient of thermal accumulation of the building with the VPS use has been defined, which characterizes the ability of the overall structure of the building to accumulate heat and reduce the temperature fluctuations in the heated premises. In the course of the study, a technique for heating premises has been developed, which allows to determine the consistent change in the temperature of air in the premises. With the help of mathematical models developed in the work, it is possible to predict and optimize thermal processes in the investigated objects.